Who Pays for Industrial Pollution Abatement? - Robinson, H. David (The Review of Economics and Statistics, 1985)
The distributional impact of industrial pollution abatement is measured for the years 1973 and 1977. The findings indicate that in 1977 1.09% of income or 0.510% of personal consumption expenditures of the lowest income class paid indirectly for abatement costs implicit in purchased goods. For the highest income class, the corresponding figures were 0.218% and 0.423%, respectively. In addition, abatement costs per dollar of output are presented for representative industries.